Survival of Salmonella in Tea Under Different Storage Conditions and Brewing Methods - Shi, Aiying; Li, Shenmiao; Ma, Hui; Du, Xin-Jun; Wang, Shuo; Lu, Xiaonan (Frontiers in Microbiology, 2022)
Salmonella is one of the leading causes of bacterial gastroenteritis. High prevalence of Salmonella in environment is partially due to its ability to enter the “viable but nonculturable” (VBNC) state when they encounter unfavourable conditions. Dried teas are traditionally believed to have a low risk of causing salmonellosis. This study investigated the survival of Salmonella in four types of dried teas under different storage conditions and brewing methods. A method that coupled propidium monoazide (PMA) and quantitative PCR was optimized to quantify VBNC Salmonella cells to assess the risk of Salmonella contamination in teas after brewing. Each tea sample was inoculated with Salmonella at an 8 log CFU/ml concentration and stored at 4°C, 10°C and 25°C. Under three storage conditions, the number of survived Salmonella was highest in teas stored at 4°C and lowest in teas stored at 25°C. After storage of 120 days, culturable Salmonella was detected from all samples ranging from 6-7 log CFU/g (4°C storage) to 3-4 log CFU/g (25°C storage). The effectiveness of brewing methods in inactivating Salmonella was assessed by brewing inoculated teas at room temperature, 55°C, 75°C and 100°C for 10 min. Brewing teas at 75°C and 100°C significantly (P < 0.05) reduced the number of viable Salmonella, but VBNC Salmonella formed when brewed at 75°C. Altogether, Salmonella can persist in dried teas for over three months at a temperature ranging from 4°C to 25°C, and thermal treatment delivered during home brewing may not eradicate Salmonella in teas.